STUDI FENOMENOLOGI PROGRAM SIARAN KENTONGAN RRI BOGOR SEBAGAI KOMUNIKASI MITIGASI BENCANA - Siti Fitriana (2020)
Bogor Regency West Java area which is located between the mountain and has a high rainfall that makes the Bogor Regency vulnerable to flood disasters, landslides and the wind of nipples. From the potential threatening catastrophe, the effort required to reduce the risk of disaster that occurred radio mass media participated in taking the role of in am to educate disaster mitigation. The theory of this study uses symbolic interactions and hypodermic theories. This research approach is qualitative with a phenomenological study. The research subject is the editorial team of RRI Bogor and the community in Bogor Regency West Java. The results of this research show that the program is broadcasting the RRI Bogor is an effective radio broadcasting program in carrying out its function as disaster mitigation communication by providing information and education about disaster that is summarized on three cycles of management of disasters, namely pre disaster, during disasters and post-disaster. In the program broadcast Kentongan has six news formats namely Voice Report, Straight News, Report On The Spot, News Feature, Filler and advertising community services. Subsequent broadcast programs have various communication strategies. The conclusion of this study explains the function and role of the program broadcast Kentongan RRI Bogor is a broadcast that bridges the media in providing education and information about disaster in Bogor. Furthermore, communication strategy used such as packing a news package as interesting as possible so that the listener or society is attracted to the broadcast Kentongan through spoken language and correct so as to influence the feeling of the listener. The advice in this research is expected the viewing hours of the program broadcast Kentongan can be broadcast every day that is from Monday to Sunday, considering the information related to the important disaster to broadcast.